Urban heat island mitigation by introducing green roof system - Lim, Chee Sam, 1991- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016